Efektivitas Program Pelayanan Pembayaran Pajak Berbasis Digital E-Samsat Melalui Aplikasi Signal - Angriani, Delvi; Rahman, Khairul (Jurnal Administrasi Politik dan Sosial, 2025)
In this study, it aims to determine how the effectiveness of the e-samsat digital-based tax payment service program through the signal application. In this study using the theory of effectiveness according to Edi Sutrisno, where there are four indicators, namely program understanding, on target, program objectives, and on time. This research uses qualitative methods and in collecting data through observation, interviews, and documentation. With data analysis using data reduction, data presentation, and conclusion drawing. Based on the analysis of the four indicators that researchers have done, it can be concluded that the e-samsat digital-based tax payment service program through the signal application is not yet effective.